1992
DOI: 10.1182/blood.v79.9.2455.bloodjournal7992455
|View full text |Cite
|
Sign up to set email alerts
|

A deletion/inversion rearrangement of the beta-globin gene cluster in a Turkish family with delta beta zero-thalassemia intermedia

Abstract: The most common forms of hereditary persistence of fetal hemoglobin synthesis (HPFH) and delta beta zero-thalassemia result from simple deletions of the beta-globin gene cluster or from point mutations in the gamma-globin gene promoters. These naturally occurring mutants extend our understanding of globin gene regulation and hemoglobin switching. Furthermore, they provide the opportunity to test in vivo hypothetical switching models that are based on the experimental approach. We report here a family with delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The identification strategy in these Germans selected for Kulozik et al (1991) for details; 3 see Kulozik et al (1993) for details; 4 see Kulozik et al (1992) for details. (Table IV).…”
Section: Heterozygous Non-immigrantsmentioning
confidence: 99%
“…The identification strategy in these Germans selected for Kulozik et al (1991) for details; 3 see Kulozik et al (1993) for details; 4 see Kulozik et al (1992) for details. (Table IV).…”
Section: Heterozygous Non-immigrantsmentioning
confidence: 99%
“…Various restriction enzyme digested fragments were hybridized with 5Ј d probe; however, the abnormal band sizes obtained were not consistent with a deletion between the d gene and the pRK 28 region, as different Eco RI, Bam HI and Hind III fragments were detected with two probes (data not shown). Combining all the gene mapping data, it was concluded that this complex arrangement is the basis for the Turkish form of deletion-inversion (db)Њ-thalassaemia which was recently described by Kulozik et al (1992). A comparison indicated that the sequence motif of the deletion breakpoint was identical to that initially described by Kulozik et al (1992), including the presence of a single orphan nucleotide (þC) at the conjunction site of the 11 .…”
Section: Resultsmentioning
confidence: 80%
“…Combining all the gene mapping data, it was concluded that this complex arrangement is the basis for the Turkish form of deletion-inversion (db)Њ-thalassaemia which was recently described by Kulozik et al (1992). A comparison indicated that the sequence motif of the deletion breakpoint was identical to that initially described by Kulozik et al (1992), including the presence of a single orphan nucleotide (þC) at the conjunction site of the 11 . 5 kb deletion and 7 .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations